1997
DOI: 10.1097/00042560-199710010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CD38 Antigen Expression on CD8+ T Cells Is a Stronger Marker for the Risk of Chronic HIV Disease Progression to AIDS and Death in the Multicenter AIDS Cohort Study Than CD4+ Cell Count, Soluble Immune Activation Markers, or Combinations of HLA-DR and CD38 Expression

Abstract: The prognostic value of several immunologic markers were compared in Los Angeles Multicenter AIDS Cohort Study (MACS) participants, most of whom had been infected with HIV for >8 years. Markers studied included CD4+ cell number, flow cytometric measurements of CD8+ cell expression of CD38 and HLA-DR antigens, and serum markers of immune activation including neopterin, beta2-microglobulin, soluble interleukin-2 receptor, soluble CD8, and soluble tumor necrosis factor receptor-alpha (TNF-alpha) type II. Cox prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
356
2
6

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 488 publications
(388 citation statements)
references
References 40 publications
24
356
2
6
Order By: Relevance
“…Immune activation has been demonstrated to play a critical role in HIV disease progression [1][2][3][4][5][6][7][8][9][10][11][12][13][14], possibly through the induction of activation-induced cell death (AICD) of bystander non-infected cells [1,43]. We have also shown here that IL-7Ra expression inversely correlates with CD4 + T cell apoptosis, and that the level of apoptosis, particularly in the memory T cell subset, is significantly altered in groups with varied IL7Ra expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune activation has been demonstrated to play a critical role in HIV disease progression [1][2][3][4][5][6][7][8][9][10][11][12][13][14], possibly through the induction of activation-induced cell death (AICD) of bystander non-infected cells [1,43]. We have also shown here that IL-7Ra expression inversely correlates with CD4 + T cell apoptosis, and that the level of apoptosis, particularly in the memory T cell subset, is significantly altered in groups with varied IL7Ra expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although many correlates have been identified that may influence the rate of HIV progression, including immune activation, and the disruption of T cell homeostasis, a complete understanding of the mechanisms of CD4 + T cell decline remains elusive [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Cytokines that signal through the common gamma chain, such as IL-2, IL-4, IL-7, and IL-15, are some of the main mediators of T cell homeostasis [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, it must be stressed that CD38 transcription is a marker for other diseases. It is prognostic for HIV infected subjects [105], chronic lymphoid leukemia [106] and for diabetic patients with nephropathy [107]. Hence reduced CD38 transcription cannot be pathognomonic for ASD but nevertheless might prove of salient clinical value in a disorder diagnosed solely using behavioral assessments reliably carried out only at the age of three [104].…”
Section: Biomarkers For Autism Spectrum Disordersmentioning
confidence: 99%
“…progression independent of the plasma viral load and peripheral blood (PB) CD4þ T-cell counts (7)(8)(9)(10)(11)(12)(13). Furthermore, CD38 expression on CD8þ T-cells correlates with HIV-1 disease progression, and it also predicts further declines in PB CD4þ T-cells (11,14).…”
mentioning
confidence: 99%